MODELING OF THE KINETIC OF SALICYLIC ACID ADSORPTION IN POLYMERIC AND ACTIVATED CHARCOAL ADSORBENTS - Câmara, L. D. T.; Silva Neto, A. J. (Revista de Engenharia Térmica, 2008)
The understanding of adsorption mechanisms of compounds utilized in many medications and prescription drugs represents an important step for the development of different separation processes of such substances. The adsorption kinetic study of such chemical compounds through the application of new models permits a better comprehension of the involved mechanisms, leading to the estimation of important parameters that will be incorporated in the equipment design. In this work a kinetic model of irreversible adsorption is implemented, which is dependent on both solute and site concentrations. It showed to be very effective correlating the simulated results with the adsorption experiments of salicylic acid through three adsorbents in different temperature conditions. The application of an inverse problem approach, with the minimization of the squared residues cost function, was successful in determining the kinetic parameters. The increase in the kinetic constants obtained with the temperature increase was followed by a reduction in the adsorption capacity of the adsorbents. Thermodynamic parameters were also estimated, leading to the comprehension about the equilibrium states of the adsorption systems considered.